The role of bacterial interference in upper respiratory tract infections in children - Brook, Itzhak (Journal of Pediatric Infectious Diseases, 2006)
Interactions between bacteria that include antagonism (interference) and synergism maintain balance between members of the normal endogenous flora, and play a role in preventing colonization by potential pathogens. Bacteria with interference capability of potential respiratory pathogens include alpha-hemolytic streptococci, non-hemolytic streptococci, and Prevotella and Peptostreptococcus spp. The role of bacterial interference in the emergence of upper respiratory tract infections and its effect on their eradication is discussed. These infections include pharyngo-tonsillitis, otitis media, and sinusitis. Treatment with antimicrobials can affect the balance between the interfering organisms and potential pathogens. Introduction into the indigenous microflora of low virulence bacterial strains that are capable of interfering with colonization and infection with virulent organisms has been used as a means of preventing the failure of antimicrobials in the treatment of pharyngo-tonsillitis and otitis media.
Keywords: Bacterial interference; alpha-hemolytic streptococcus; anaerobic bacteria; otitis media; tonsillitis